Pemberdayaan Masyarakat di Bidang Pertanian dan Peternakan: Studi Kasus Desa Nambo Kabupaten Bogor, Provinsi Jawa Barat - Nur Afmi Muniroh; Bahari Setia Panji Nugraha; Ninuk Purnaningsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The study was conducted in Nambo Village, Klapa Nunggal District, Bogor Regency, West Java Province. As many as 80% of Perhutani's land has not yet been opened and utilized by the community. Land clearing is carried out based on social entrepreneurship. Although carried out by means of socialization published in the community itself, who do not know information about agriculture and villages supported by the information system, thus the information system can help in the delivery and obtaining various needs such as social entrepreneurship. Research Objectives (1) Studying the process of community empowerment based on social entrepreneurship in agriculture and animal husbandry (2) helping the development of information system 4.0 through the website (3). This research method is qualitative with descriptive data analysis of Grounded Theory Approach research design techniques. The sample used was purposive sampling from 24 people selected. Data collection is done through observation, interviews and documentation. Data validation is done with member approval. Data analysis uses open, axial and selective codes. The results showed that the process of community empowerment through stages (1) Awareness, involving community leaders as instructors, mobilizers, motivators and role models, (2) Capacitation, through training activities, (3) Empowerment, through community assistance. Supporting factors for social entrepreneurship are (a) Initial capital, (b) Active participation of farmers and livestock groups, and (c) the role of community leaders. Inhibiting factors of social entrepreneurship and information system development 4.0 are (a) Low leadership, (b) Lack of human resources (c) Lack of capacity in agriculture and animal husbandry, (d) Lack of knowledge about information systems and (e) Limited to seeking information. Keywords: community empowerment, agriculture and animal husbandry, social entrepreneurship, information systems